De-Sakralisasi dalam Pembelajaran Bahasa Arab di Indonesia: Analisis Bahasa sebagai Identitas Agama - Yahya, Yuangga Kurnia; Mahmudah, Umi; Muhyiddin, Luthfi (JLA (Jurnal Lingua Applicata), 2020)
Learning Arabic in Indonesia is still relatively minimal when compared with other foreign language lessons. One reason is that religious orientation in learning makes it an exclusive and limited subject. This study aims to describe the religious orientation in learning Arabic and its influence on the interest in learning Arabic in Indonesia. This research is a qualitative research by collecting data from several sites that discuss the urgency of learning Arabic for the people of Indonesia. The top five sites with these keywords are Rumaysho.com, BelajarIslam.com, Islampos.com, Kompasiana.com, and kiblat.net. The reasons in studying Arabic from five sites will be classified according to learning orientation that includes religious, academic, professional, and economic orientation. The most dominant orientation will be analyzed with the approach of language and identity of Yasir Suleiman's perspective on two functions of language, as an instrument of communication and as a symbol of identity. This research found that stereotyping of Arabic makes it even more exclusive and closed to non-Muslims in Indonesia. Learning Arabic itself is not only limited to religious orientation, but makes it as the function of language itself, as an instrument of communication.